Теоретичні аспекти управлінської структури системи маркетингу на підприємстві - Крючко, Леся Станіславівна; Kryuchko, Lesya; Лозовий, Д. В.; Lozovyi, D. V.; Беззей, К. С.; Bezzei, K. S.; Терещенко, Я. І.; Tereshchenko, Y. I.; Майоров, К. Д.; Mayorov, K. D. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2023)
Посилення ринкової конкуренції в сучасному світі вимагає від учасників ринку швидко реагувати на зміну вимогу мов і пропозицій на ринку. Більшість підприємств успішно конкурують і підсилюють свої позиції швидко реагуючи на зміни зовнішньої та внутрішньої маркетингового середовища. Основною складовою внутрішнього середовища підприємства є управлінська координуюча система у вигляді комплексної, ефективної, внутрішньої організаційної структури. Комплексні організаційні маркетингові структури не створюються миттєво. Більшість підприємств долають певний шлях розвитку і ускладнення бізнес процесів і функцій які потребують комплексної ієрархічної організації і обслуговування силами маркетингових фахівців. Ефективна організаційна структура маркетингу може мати різні форми. Може бути простою і вміщувати декілька ланок займаних по одиничними фахівцями, а може бути комплексною з десятків різних рівнів і з сотень співробітників і керівників. Increasing market competition in today's world requires market participants to quickly respond to changes in market conditions and offers. Most companies successfully compete and strengthen their positions by quickly responding to changes in the external and internal marketing environment. The main component of the internal environment of the company is the managerial coordinating system in the form of a complex, effective, internal organizational structure. Complex organizational marketing structures are not created instantly. Most companies overcome a certain path of development and complication of business processes and functions that require complex hierarchical organization and maintenance by marketing specialists. An effective marketing organizational structure can take many forms. It can be simple and include several links occupied by individual specialists, or it can be complex with dozens of different levels and hundreds of employees and managers. At the current stage of dynamically changing market processes, which of the main problems of the company’s competitiveness is a problem development of the organizational structure of the marketing system in the process business scaling. The most important factor affecting performance marketing activity, the company chooses the optimal and appropriate situation organizational marketing structure. Delayed implementation of changes causes significant risks and negatives research for the company. Analysis and assessment of the factors of the changing marketing environment, provide competitive advantages and contribute to dynamic business development of the company. In general, in each organizational structure, the main ones can be distinguished elements that are similar in each of the different structures are located among themselves in a certain sequences from the lower to the upper level that makeup the hierarchy structure and form hierarchical relationships. At the lower level of the management structure are ordinary employees who no one obeys and who do not have broad powers. Though that lower level professionals do not have power, they have significant influence on the results of the enterprise. Such specialists make up the majority of companies and it is they who best understand the needs of the market and the company's customers, but they do not affect strategic decision-making in the least.
Theoretical aspects of the administrative structure of the marketing system at the enterprise
Keywords: координуюча система; coordinating system; маркетинг; marketing; структура маркетингу; marketing structure; синтез; synthesis; аналіз; analysis; структура управління; management structure; товарна політика; product policy; споживач; consumer